2021
DOI: 10.32604/fdmp.2021.016710
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation and Experimental Analysis of the Influence of Asymmetric Pressure Conditions on the Splitting of a Gas-Liquid Two-Phase Flow at a T-Junction

Abstract: Dedicated experiments and numerical simulations have been conducted to investigate the splitting characteristics of a gas-liquid two phase flow at a T junction. The experiments were carried out for different gas-liquid velocities. The flow rates in the two branches were measured accurately to determine how the two considered phases distribute in the two outlets. The experimental results have shown that when the two outlet pressures are asymmetric, the two-phase flow always tends to flow into the outlet which h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…The distribution of these flows can be uneven, influenced by factors such as the unpredictable nature of the two-phase flow at the T-junction's entrance and the unequal conditions in the pipelines downstream of the T-junction. The so-called uneven distribution phenomenon has two meanings: one is in which the GLTPF passes through the T-junction, the GLTPF has a different gas-liquid ratio in the downstream parallel pipelines, and the other is an uneven flow distribution in the downstream parallel pipelines [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of these flows can be uneven, influenced by factors such as the unpredictable nature of the two-phase flow at the T-junction's entrance and the unequal conditions in the pipelines downstream of the T-junction. The so-called uneven distribution phenomenon has two meanings: one is in which the GLTPF passes through the T-junction, the GLTPF has a different gas-liquid ratio in the downstream parallel pipelines, and the other is an uneven flow distribution in the downstream parallel pipelines [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For the impact T-junction with two outlet arms connecting the riser, Liu et al [6] showed that the inlet and outlet pressures had a great influence on the gas-liquid two-phase mass flow rate. Ma et al [7] numerically simulated the gas-liquid two-phase flow distribution in a branch pipeline, demonstrating that, at the same outlet pressure, the gas-liquid two-phase flow was always in a uniform distribution state. Ma et al [8,9] explored the asymmetry of the downstream pipeline with the aim to obtain the equal gasliquid ratio separation of the gas-liquid two-phase flow.…”
Section: Introductionmentioning
confidence: 99%
“…Reliable reservoir models can accurately reproduce the complete reservoir developing process and provide convincing guidance for production management decision-making [1][2][3][4][5]. History matching that can correct reservoir model parameters based on geological information and production data is a critical step in reservoir numerical simulation process.…”
Section: Introductionmentioning
confidence: 99%